The Receding Cosmic Shoreline of Mid-to-late M Dwarfs: Measurements of Active Lifetimes Worsen Challenges for Atmosphere Retention by Rocky Exoplanets - Emily K. Pass; David Charbonneau; Andrew Vanderburg (The Astrophysical Journal Letters)
Detecting and characterizing the atmospheres of terrestrial exoplanets is a key goal of exoplanetary astronomy, one that may now be within reach given the upcoming campaign to conduct a large-scale survey of rocky M-dwarf worlds with the James Webb Space Telescope. It is imperative that we understand where known planets sit relative to the cosmic shoreline—the boundary between planets that have retained atmospheres and those that have not. Previous works modeled the historic X-ray and ultraviolet (XUV) radiation received by mid-to-late M-dwarf planets using a scaling relation calibrated using more massive stars, but fully convective M dwarfs display unique rotation/activity histories that differ from Sun-like stars and early M dwarfs. We synthesize observations of the active lifetimes of mid-to-late M dwarfs to present an updated estimate of their historic XUV fluence. For known planets of inactive, mid-to-late M dwarfs, we calculate a historic XUV fluence that is 2.1–3.1 times the canonical XUV scaling relation on average, with the larger value including corrections for the pre-main-sequence phase and energetic flares. We find that only the largest terrestrial planets known to orbit mid-to-late M dwarfs are likely to have retained atmospheres within the cosmic shoreline paradigm. Our calculations may help to guide the selection of targets for JWST and may prove useful in interpreting the results; to this end, we define a novel atmosphere retention metric (ARM) that indicates the distance between a planet and the cosmic shoreline, and tabulate the ARM for known mid-to-late M-dwarf planets.